Tindak Pidana Persetubuhan Yang Dilakukan Oleh Anak Terhadap Anak(studi terhadap putusan pengadilan negeri karanganyar No. 02/Pid.Sus-Anak/2014/PN Krg) - Hutomo, Hanindyo Imam; , Muchamad Iksan, S.H., M.H (2016)
The purpose of this research is to determine the application of criminal law material to children who commit criminal acts against children sexual intercourse, as well as understanding the legal reasoning that used by judges to impose criminal penalties against child perpetrators of criminal acts against. The method used this paper adalan normative methods of qualitative data analysis. The data source consists of primary data, interviews and secondary data, legal data primary, secondary and tertiary. Data were collected by literature study and interviews and then analyzed qualitatively. Collection methods used in the form of literature studies aimed at obtaining secondary data and field research in the form of interviews to obtain primary data. The results showed that the imposition of criminal penalties on the child must promote peace fakator that restorative justice can be done. The criminal act of decency is complaint-based offense which even forgiving factor can not abolish crime. Age limit of children who can dipersidangkan in juvenile court is not decisive that a child can be in the process of law under Act No. 35 of 2014 on the Amendment of Act No. 23 of 2002 regarding Child Protection.